The period of the witch trials - Ankarloo, Bengt (Witchcraft and magic in Europe, 2002)
The fifteenth to eighteenth centuries was a period of witchcraft prosecutions throughout Europe and modern scholars have now devoted a huge amount of research to these episodes. This volume will attempt to bring this work together by summarising the history of the trials in a new way - according to the types of legal systems involved. Other topics covered will be the continued practical use made of magic, the elaboration of demonological theories about witchcraft and magic, and the further development of scientific interests in natural magic through the ''Neoplatonic'' and ''Hermetic'' period.